Direito fundamental ao trabalho digno e o contrato de trabalho intermitente - Laraia, Maria Ivone Fortunato (2018)
The intermittent labor contract, provided for in the text of article 452-A of the Consolidation of Labor Laws, a mechanism added by labor reform (Law 13467/17), is a contract in which the rendering of service, with subordination, is not continuous, with periods of actual work and inactivity, and can be determined by hour, day or month of work and without a fixed journey. It was conceived to be one of the solutions found for the serious Brazilian economic crisis, since it aims to create jobs, modernize labor laws and increase the competitiveness of Brazilian companies, facing the demands of contemporary capitalism. The intermittent contract, as it was instituted, breaks with the logic of the standard employment bond and contributes to the precariousness of the employment relations, since it allows the use of labor in a discontinuous way; authorizes the payment of salaries lower than the minimum constitutionally guaranteed; violates the principles of human dignity and the social value of work, improves the social status of the worker and offends the right to paid annual leave, at least one third more than the normal salary of the worker, rendering building a free, fair and supportive society, with the eradication of poverty and the reduction of social inequalities, thus failing to promote the welfare of all. This paper presents a proposal for a bill, inspired by Portuguese and Italian legislation, in order to enable the intermittent employee to carry out fundamental social rights, especially human dignity